(untitled) (Heritage, 2022)
Front fortification towards Bulgaria, especially Pirot’s positions, outposts of Nišavski direction, is the consequence of concern of Yugoslav military top for Eastern border securing. This fear was justified if there were taken into account relationships between two countries which were mostly marked with wars. From military point of view, Nišavski direction was sensitive for both sides. For Bulgarian side, that was the shortest way by which Sofia could be threatened. Yugoslav side feared the deterioration of Niš, thus disconnection of the important Moravsko-Vardarska communication. All war plans of Yugoslav army have foreseen at that direction the concentration of strong forces, and additional fortification as well so that to make use of natural obstacles. Nevertheless, foreign policy-related circumstances in the 1920s and 1930s, facing with highly more aggressive neighbour such Italy, and later on Germany, led Yugoslav General Staff to secure, among all, Northern and Western borders. Border securing with Bulgaria was approached only in 1940, after its join to Triple Pact. The works were interrupted by the beginning of April’s war, and unfinished fortifications represented none obstacle for breakthrough of German forces.